LPCAT1 as a prognostic biomarker and risk indicator for hepatocellular carcinoma: insights into genes related to lipid metabolism - Zhai, Hang; Wang, Jicai; He, Yongfei; Hong, Shengjie; Huang, Kai; Hu, Shuai; Xu, Junming; Hao, Shuang; Zhang, Guangquan; Shi, Xianjie (Frontiers in Oncology, 2026)
BackgroundHepatocellular carcinoma (HCC) is a lethal malignancy. Lipid metabolic reprogramming influences therapy response, but its prognostic value is undefined.MethodsFrom TCGA and GEO data, we derived an 8-gene lipid metabolism-related risk score (LMrisk) via LASSO regression. Its associations with tumor immunity and drug sensitivity were analyzed. The lead gene, LPCAT1, was functionally assessed in vitro.ResultsThe LMrisk signature robustly stratified patient survival in both cohorts. Integrated analysis identified LPCAT1 as a hub gene. Its overexpression in HCC cells potently enhanced proliferation, migration, and invasion.ConclusionLPCAT1 is a vital prognostic biomarker and putative therapeutic target in HCC.